2015
DOI: 10.1590/1516-3180.2014.8251809
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Mycobacterium avium subsp. paratuberculosis (MAP) in Brazilian patients with inflammatory bowel diseases and in controls

Abstract: This study does not provide evidence for a role of MAP in the etiology of CD, although MAP DNA was detected in all three patient groups. This is the first report of MAP presence in human intestinal biopsies in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Several bacteria have been ascribed the ability to translocate across gastrointestinal mucosa and survive the host immune response; the most prominent of these are adherent-invasive Escherichia coli (AIEC) 34 and Mycobacterium avium subspecies paratuberculosis (MAP). 35,36 The molecular techniques employed in this study cannot identify AIEC specifically; however, it is notable that Escherichia/Shigella represented an average 8.8% of the bacteria isolated from lymph nodes. In previous studies, Escherichia/Shigella has been shown to contribute only 0.4% of the microbial mass in patients with IBD 37 and even less in healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…Several bacteria have been ascribed the ability to translocate across gastrointestinal mucosa and survive the host immune response; the most prominent of these are adherent-invasive Escherichia coli (AIEC) 34 and Mycobacterium avium subspecies paratuberculosis (MAP). 35,36 The molecular techniques employed in this study cannot identify AIEC specifically; however, it is notable that Escherichia/Shigella represented an average 8.8% of the bacteria isolated from lymph nodes. In previous studies, Escherichia/Shigella has been shown to contribute only 0.4% of the microbial mass in patients with IBD 37 and even less in healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…Detection of MAP in 2–4 million patients with ulcerative colitis (UC) has been documented/speculated upon [ 73 ]. However, only 13 research documents considered MAP in connection to UC throughout the study period [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Growth of MAP research linked with UC had a negative growth rate of –30% ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study constitutes a continuation of a previous one, described by Carvalho, et al (2015), in which the aim was to verify if there was difference in the detection and quantification of MAP DNA in intestinal samples from patients with IBD, mainly CD, and patients without IBD, which underwent colonoscopy between the years 2009 and 2011 by real-time PCR [6]. The present study analysed the same population, studying the risk factors that could be influencing the occurrence of MAP, identified in the previous study, in these samples, independently of the diagnosis (IBD or non-IBD).…”
Section: Samples and Study Designmentioning
confidence: 66%
“…Therefore, data collection for the case-control study was conducted from 2013 to 2015 at the same reference institute and with the same population [6]. Patients who had positive biopsies for MAP DNA in the previous study were considered cases.…”
Section: Samples and Study Designmentioning
confidence: 99%
See 1 more Smart Citation